Acute Repiratory Distress Syndrome in cancer patients: Epidemiology, risk factors and outcomes - Cardoso, Eduardo Mantovani; Tomadon, Aniele; Lovison, Keli; Schmidt, Raysa Cristina; Chung, Thais Tsing; Duarte, Pericles Almeida Delfino (European Journal of Oncology and Environmental Health, 2018)
Purpose: This study aimed to evaluate the incidence and outcomes of Acute Respiratory Distress Syndrome (ARDS) in adult oncological patients in the ICU of a dedicated cancer hospital, as well as analyse the risk and protective factors associated with mortality in this population. Methods: A prospective cohort study evaluating all adult cancer patients admitted to the ICU, from January 2012 to December 2013. Results: The incidence of ARDS (n=87) was 11.9% of cancer patients in the ICU, and 17.8% among those in mechanical ventilation. ARDS was more common in onco-hematological patients. Patients with ARDS had longer ICU length of stay, more complications (mainly acute kidney injury [AKI]) and mortality than non-ARDS patients. Among patients with ARDS, those with a later ARDS onset (>48 h hospitalised) and with a more positive Fluid Balance (FB) had a higher mortality incidence. No differences were found in the ventilatory parameters, although the patients who died presented reduced pulmonary static compliance. Conclusions: The incidence and morbimortality of ARDS were high (particularly in onco-hematological patients). Later onset ARDS and highly positive FB presented a trend to a higher mortality.